Level of knowledge and perceived level of competency of oncology nurses in palliative care in a tertiary hospital - Alvarez, Euzel Aubrey R.; Ares, Marie Bernadette P.; Buan, Sherrie Anne S.; Esguerra, Cyrus A.; Gayo, Kerima Danica L.; Ordoña, Michael Gino A.; Palisoc, Mary Camille E.; Samentar, Neana Kris N.; Vallejos, Anatole Gail P. (Manila College of Nursing University of the Philippines Manila, 2014)
Palliative care is an essential part of nursing care that alleviates pain and discomfort. Few studies in the Philippines have explored about it. This research aims to describe the relationship between the level of knowledge and perceived level of competence of oncology nurses in a tertiary hospital. A descriptive and correlational research design was used. Oncology nurses in the Philippine General Hospital, the target population, were given survey questionnaires measuring their level of knowledge in palliative care and perceived level of competence in cancer using the Palliative Care Quiz for Nursing Tool and CANO Oncology Nurses Education Project Self-Assessment Tool, respectively. The mean scores of the 20 participants in 6 subheads of CONEP self-assessment tool yielded under proficiency. One subhead, management of cancer symptoms and treatment of side effects, yielded a mean score under competent category. Formal trainings and continuing education were considered for the educational background of the population. Formal trainings revealed statistical significance (t=0.012; p<0.050); at 95% confidence interval, there is sufficient evidence to say that those who had formal training had higher mean scores than those who didn’t. Results showed weak negative linear relationship between level of knowledge in palliative care and perceived level of competency, though statistically insignificant. In six out of seven subheads in the CONEP Self-Assessment Tool, majority of the nurses rated themselves as Proficient. Using the PCQN tool, the participants yielded a mean score of 9.3 (46.5%). There is weak, negative significance between the current level of knowledge and the perceived level of competency on palliative care of the population. Formal training was found to have a significant relationship with the level of knowledge of the nurses in palliative care.
Research (In partial fulfillment of the requirements of the course N121.1: Intensive Nursing Experience, Hospital-based) -- University of the Philippines Manila, April 2014.
Keywords: Intensive nursing experience -- Hospital-based.